2012
DOI: 10.4067/s0716-97602012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in vitro plant regeneration from leaf explants of Launaea sarmentosa (Willd.) Sch. Bip. ex Kuntze

Abstract: An efficient protocol for organogenesis through leaves has been established for Launaea sarmentosa (Willd.) Sch. Bip. ex Kuntze, a highly valuable medicinal plant. The leaf explants produced microshoots on MS basal medium when fortified with cytokinins and auxins. A combination of 6-benzylaminopurine (BAP) at 0.5mg/l and naphthaleneacetic acid (NAA) at 0.2mg/l resulted in the induction of high frequency microshoots in 30 days. The microshoots were successfully subcultured for shoot elongation and eventually fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…On the contrary positive synergistic effect of cytokinins like BAP or Kn or TDZ or 2iP or zeatin in combination with an auxin like IAA, or NAA on in vitro shoot regeneration through organogenic differentiation has been reported by several workers (Shen et al 2007, Unda et al 2007, Erisen et al 2010, Ghimire et al 2010, Lin et al 2011, Wadl et al 2011, Mandal and Laxminarayana 2012, Perez-Jimenez et al 2012and Bhagya et al 2013. Superior effect of BAP for shoot multiplication has been reported among various medicinal plants of Asteraceae, like Tanacetum cinerariifolium (Hedayat et al 2009), Spilanthes acmella (Saritha and Naidu 2008), Launaea sarmentosa (Mahesh et al 2012). As in the present study, the reduction of shoot regeneration potential by the combined effect of BAP and GA 3 compared to a medium with cytokinin alone was also demonstrated in Guizotia abyssinica (Baghel and Bansal 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary positive synergistic effect of cytokinins like BAP or Kn or TDZ or 2iP or zeatin in combination with an auxin like IAA, or NAA on in vitro shoot regeneration through organogenic differentiation has been reported by several workers (Shen et al 2007, Unda et al 2007, Erisen et al 2010, Ghimire et al 2010, Lin et al 2011, Wadl et al 2011, Mandal and Laxminarayana 2012, Perez-Jimenez et al 2012and Bhagya et al 2013. Superior effect of BAP for shoot multiplication has been reported among various medicinal plants of Asteraceae, like Tanacetum cinerariifolium (Hedayat et al 2009), Spilanthes acmella (Saritha and Naidu 2008), Launaea sarmentosa (Mahesh et al 2012). As in the present study, the reduction of shoot regeneration potential by the combined effect of BAP and GA 3 compared to a medium with cytokinin alone was also demonstrated in Guizotia abyssinica (Baghel and Bansal 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro propagation through organogenesis from cotyledons was described here for this plant. Among Asteraceae members, direct and indirect organogenesis has been achieved with Stevia rebaudiana using thin cell layers of hypocotyls (Marco and Lourdes 2015), Artimisia vulgaris using cotyledonary nodes (Kumar and Kumari 2010), Cinnamomum tamala using nodal segment, shoot tip, internode and leaf (Sharma and Nautiyal 2009), Eclipta alba using leaf, stem and root (Zafar and Sagar 1999), Launaea sarmentosa using leaves (Mahesh et al 2012), Spilanthes acmella using leaf discs (Singh and Chaturvedi 2012) etc. In the present study, the effect of BAP either alone or in combination with IBA or GA 3 was evaluated on multiple shoot induction on cotyledons of B. subsessile.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained shoots, independent of the source of initial explants developed normally without hyperhydratises symptoms. In previous reports on the regeneration of Launaea sarmentosa, Mahesh et al, (2012) also observed healthy shoots of good conditions on a high BAP concentration combined with a low NAA, Rhizogenesis was not observed in any type of explants used for regeneration of I. germanica in both the initial material and subsequent subcultures. BAP is known as a very effective growth regulator for shoot multiplication among members of Asteraceae family.…”
Section: Rooting and Acclimatizationmentioning
confidence: 99%
“…Most of these studies focused on obtaining an efficient system for in vitro propagation of crop or medical importance plants, e.g. Echinacea purpurea (Zobayed and Saxena, 2003) or Carthamus tinctorius (Kumar and Kumari, 2011) via somatic embryogenesis, while regeneration by organogenesis has been developed for Heliantus annus (Ozyigit et al, 2007), Launaea sarmentosa (Mahesh et al, 2012), and many others (Amin et al, 2013). Moreover, efficient and rapid clonal regeneration method has been shown to be a great tool in the protection of rare and threatened species of the Asteraceae family e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Launaea sarmentosa has been traditionally used as a folk remedy in India. It has been used traditionally in the treatment of jaundice, blood disorders, allergy, and gout [25,99].…”
Section: Asteraceaementioning
confidence: 99%